2013
DOI: 10.3390/ijms140815459
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Signal-Regulating Kinase 1 Is Involved in Brain-Derived Neurotrophic Factor (BDNF)-Enhanced Cell Motility and Matrix Metalloproteinase 1 Expression in Human Chondrosarcoma Cells

Abstract: Chondrosarcoma is the primary malignancy of bone that is characterized by a potent capacity to invade locally and cause distant metastasis, and is therefore associated with poor prognoses. Chondrosarcoma further shows a predilection for metastasis to the lungs. The brain-derived neurotrophic factor (BDNF) is a small molecule in the neurotrophin family of growth factors that is associated with the disease status and outcome of cancers. However, the effect of BDNF on cell motility in human chondrosarcoma cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 58 publications
(58 reference statements)
0
21
0
Order By: Relevance
“…In our study, the expression of p-p38 and p-JNK were upregulated in the SDH of our CYP-induced cystitis model, suggesting the activation of p38/JNK signaling pathway. In addition, ASK1-dependent p38/JNK was reported as a downstream molecule of the BDNF signaling pathway [49]. BDNF-TrkB signaling regulates the progress of p38/JNK signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the expression of p-p38 and p-JNK were upregulated in the SDH of our CYP-induced cystitis model, suggesting the activation of p38/JNK signaling pathway. In addition, ASK1-dependent p38/JNK was reported as a downstream molecule of the BDNF signaling pathway [49]. BDNF-TrkB signaling regulates the progress of p38/JNK signaling.…”
Section: Discussionmentioning
confidence: 99%
“…In human cervix carcinoma cells, p38MAPK activation may be a key upstream signal of TNF-α-induced apoptosis and attenuation of the p38MAPK pathway by overexpression of DDB2 (a DNA repair protein) may be responsible for acquired TNF-α resistance (31). ASK1, a MAPKKK activated in cells treated with TNF-α, activates MKK3/MAPKK6 (or MKK6) and p38MAPK in turn, thus inducing apoptosis (32). However, another study demonstrated that ASK1 mediates anti-apoptotic signals (33).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that this augmentation in resting BDNF concentration is linked to an increase in enzymatic profile, which is responsible for extracellular cleavage of BDNF, and physical exercise influences this constitutive context. It has been found that chronic exercise seems to be closely related to activation of matrix metalloproteinases (38) and increased plasmin (16), which is mainly responsible for extracellular cleavage of BDNF (27,41), which are related to angiogenesis processes mediated by increases in serum BDNF concentration (19,20,41).…”
Section: Discussionmentioning
confidence: 99%